Coating process based on wet-process phosphoric acid

The phosphorus-aluminum envelope agent is prepared by wet phosphoric acid and aluminum hydroxide and combined with sodium metaaluminate, which solves the problem of reducing the pass rate of titanium dioxide when using wet phosphoric acid, and achieves the effect of reducing costs and maintaining quality.

CN119752221AActive Publication Date: 2025-04-04XIANGYANG LOMON TITANIUM IND CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411956137.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-04-04
Estimated Expiration
2044-12-28

AI Technical Summary

Technical Problem

In order to ensure the quality of titanium dioxide in the prior art, high-purity pyrophosphoric acid is usually used as the envelope agent. Although the cost is high, if wet phosphoric acid is used instead, the pass rate of titanium dioxide will be reduced.

Method used

The phosphorus aluminum envelope agent is prepared by wet phosphoric acid and aluminum hydroxide. The phosphorus aluminum envelope agent is obtained by maturation and filtration, and combined with sodium metaaluminate solution by co-flow method to be used for the surface treatment of titanium dioxide.

Benefits of technology

It is realized that using wet phosphoric acid instead of ignition phosphoric acid without reducing the pass rate of titanium dioxide is used to reduce production costs and avoid the increase in cost caused by the use of sulfuric acid to neutralize sodium hydroxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215889410000061
    Figure BDA0005215889410000061
  • Figure BDA0005215889410000071
    Figure BDA0005215889410000071
Patent Text Reader

Abstract

The invention discloses a coating process based on wet-process phosphoric acid, and belongs to the technical field of titanium dioxide production. According to the invention, the problem of coating by replacing pyrogenic process phosphoric acid with wet process phosphoric acid on the premise of not influencing the qualification rate of titanium dioxide is solved. The preparation method adopts a sodium metaaluminate solution and a phosphorus-aluminum coating agent. The preparation method of the phosphorus-aluminum coating agent comprises the following steps: S1, mixing wet-process phosphoric acid and aluminum hydroxide to obtain a mixture; s2, curing the mixture; and S3, filtering and diluting the cured product to obtain the phosphorus-aluminum coating agent. The phosphorus-aluminum coating agent is prepared from wet-process phosphoric acid and aluminum hydroxide, the aluminum hydroxide reacts with the wet-process phosphoric acid to form aluminum phosphate which is soluble salt, and iron ions can generate precipitates when the pH value is 2.7, so that redundant iron ions can be removed through filtration, and the relatively pure phosphorus-aluminum coating agent can be obtained; compared with the wet-process phosphoric acid purification before use, the cost is lower, and the quality of the titanium dioxide cannot be influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium dioxide production, and in particular relates to a coating process based on wet-process phosphoric acid. Background Art

[0002] LR-952 titanium dioxide is coated with phosphoric acid and sodium aluminate to improve the light resistance of the product in decorative laminated paper. Since the product was put on the market, its light resistance in laminated paper has been widely recognized by users.

[0003] Phosphoric acid is divided into two types according to the preparation method: pyrophosphoric acid and wet-process phosphoric acid. Pyrophosphoric acid has high purity, but the power consumption of yellow phosphorus production is high, and the product cost is relatively high. Wet-process phosphoric acid is to decompose phosphate rock powder with inorganic acid, separate crude phosphoric acid, and then purify it to obtain phosphoric acid products. Therefore, in order to ensure the quality of titanium dioxide, phosphoric acid using pyrophosphoric acid with higher purity is used in the prior art. If wet-process phosphoric acid is used instead of pyrophosphoric acid, although the cost is reduced, the qualified rate of titanium dioxide will also be reduced. Summary of the invention

[0004] In view of the problem in the prior art of how to use wet-process phosphoric acid instead of pyrogenic phosphoric acid for coating without affecting the qualified rate of titanium dioxide, the present invention provides a coating process based on wet-process phosphoric acid.

[0005] The technical solution adopted by the present invention is as follows:

[0006] A coating process based on wet phosphoric acid is carried out using a sodium aluminate solution and a phosphate-aluminum coating agent. The preparation method of the phosphate-aluminum coating agent comprises the following steps:

[0007] S1: mixing wet-process phosphoric acid and aluminum hydroxide to obtain a mixture;

[0008] S2: ripening the mixture;

[0009] S3: Filter and dilute the matured product to obtain a phosphate-aluminum coating agent.

[0010] Preferably, the molar ratio of wet-process phosphoric acid to aluminum hydroxide in S1 is 3:1.

[0011] Preferably, the amount of wet-process phosphoric acid added in S1 is 6.2 m 3 , the amount of aluminum hydroxide added is 2t.

[0012] As a preferred embodiment, the filtering condition in S3 is that the filter cloth is polypropylene and the air permeability is 30L / m 3 ·s.

[0013] Preferably, the concentration of the aluminum-phosphorus coating agent in S3 is 100-120 g / L in terms of P2O5.

[0014] Preferably, the specific steps of encapsulation are as follows:

[0015] S41: injecting a quantitative titanium dioxide slurry into a coating device, stirring, measuring the concentration and adjusting it to within a qualified range to obtain slurry A;

[0016] S42: adding a phosphate aluminum coating agent to slurry A, adjusting the pH, and aging to obtain slurry B;

[0017] S43: adding a phosphate aluminum coating agent and a sodium aluminate solution to slurry B in parallel, and aging to obtain slurry C;

[0018] S44: adding the sodium aluminate solution into the slurry C, and obtaining the slurry D after aging;

[0019] S45: adding aluminum sulfate solution and sodium aluminate solution to slurry D in parallel, and obtaining slurry E after aging;

[0020] S46: Adjust the pH value of slurry E to obtain coated titanium dioxide slurry.

[0021] Preferably, the total mass ratio of the phosphorus aluminum coating agent added in S42 and S43 to titanium dioxide is 2.2-3% in terms of P2O5, and the pH value of the slurry C obtained after aging is controlled to be 6.0-7.5.

[0022] Preferably, the pH value of the slurry D obtained after aging is 8.0-8.5.

[0023] Preferably, the total mass ratio of sodium aluminate and aluminum sulfate added in S43, S44 and S45 to titanium dioxide is 5.0-6.0% in terms of Al2O3, and the pH value of the slurry S45 obtained after aging is 8.0-8.5; the pH value of the coated titanium dioxide slurry obtained in S46 is 5.5-6.0.

[0024] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0025] The present invention prepares a phosphorus-aluminum coating agent from wet-process phosphoric acid and aluminum hydroxide, and the aluminum hydroxide reacts with the wet-process phosphoric acid to form a soluble salt such as aluminum phosphate, which is used as a coating agent for the surface treatment of titanium dioxide, thereby avoiding the existing sodium aluminate prepared by aluminum hydroxide and sodium hydroxide as a coating agent, but in order to adjust the pH during the coating process, sulfuric acid is used to neutralize sodium hydroxide, resulting in a problem of increased cost. Since the main difference between wet-process phosphoric acid and pyrogenic phosphoric acid is that the iron content in wet-process phosphoric acid is greater than the iron content in pyrogenic phosphoric acid, and iron ions will precipitate at pH 2.7, excess iron ions can be removed by filtering to obtain a relatively pure phosphorus-aluminum coating agent, which is lower in cost than purifying wet-process phosphoric acid before use, and will not affect the quality of titanium dioxide. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the present application will be clearly and completely described in combination with the embodiments of the present application below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0027] Example 1

[0028] A coating process based on wet-process phosphoric acid comprises the following steps:

[0029] S1: At a temperature of 90°C, 6.2 m 3 Wet-process phosphoric acid and 2t of aluminum hydroxide are mixed and reacted for 90 minutes to obtain a mixture;

[0030] S2: maintaining the temperature at 90° C. to mature the mixture for 55 to 65 minutes, 60 minutes in this embodiment;

[0031] S3: The matured product is first filtered using a filter press. The filtering conditions are that the filter cloth is polypropylene and the air permeability is 30L / m 3 ·sThen the obtained filtrate is diluted until the concentration of the phosphate-aluminum coating agent is 100-120 g / L in terms of P2O5. The concentration of the phosphate-aluminum coating agent obtained in this embodiment is 110 g / L in terms of P2O5;

[0032] The titanium dioxide is coated by a parallel flow method using a sodium aluminate solution and a phosphorus aluminum coating agent prepared by S3. The specific steps are as follows:

[0033] S41: injecting titanium dioxide slurry (in terms of TiO2) into a coating device, stirring and measuring the concentration and adjusting it to within a qualified range to obtain slurry A. In this embodiment, the concentration of slurry A is 300 g / L in terms of TiO2;

[0034] S42: Adding a phosphate-aluminum coating agent to slurry A at a temperature of 70°C, wherein the amount of the phosphate-aluminum coating agent added is x times the amount of the titanium dioxide slurry added. 101 %, adjust the pH to 6.0, and ripen for 15 minutes to obtain slurry B;

[0035] S43: Adding a phosphate aluminum coating agent and a sodium aluminate solution to slurry B at a temperature of 70°C in parallel, wherein the amount of the phosphate aluminum coating agent added is x times the amount of the titanium dioxide slurry added. 201 %, and X 101 %+X 201 % = 2.2%, when pH drops to 6.0, sodium aluminate solution is added to control pH 6.0-7.5. The concentration of sodium aluminate solution is 220g / L in terms of Al2O3. The amount added is Y 101%, the addition time is 60min, and slurry C is obtained after aging;

[0036] S44: Add sodium aluminate solution (concentration is the same as S43) to slurry C at a temperature of 70°C, wherein the amount of sodium aluminate solution is Y 201 %, the addition time was 20 min, and slurry D was obtained after aging for 20 min. After adding sodium aluminate solution, the pH of the slurry was 8.0;

[0037] S45: At a temperature of 70°C, aluminum sulfate solution with a concentration of 90 g / L in terms of Al2O3 and sodium aluminate solution (the concentration is the same as S43) are added to slurry D in parallel, wherein the amount of sodium aluminate added is Y 301 %, the amount of aluminum sulfate solution added is Y 401 %, and calculated as Al2O3 101 %+Y 201 %+Y 301 %+Y 401 % = 5.0%, and Y is calculated as Al2O3 301 %:Y 401 % = 2:1, the duration of the parallel flow is 130 min, the pH after the parallel flow is 8.0, and the slurry E is obtained after aging for 30 min;

[0038] S46: After adding dilute sulfuric acid to adjust the pH value of slurry E to 5.5, coated titanium dioxide slurry is obtained. The titanium dioxide slurry is washed, flash evaporated, and steam-powdered to obtain coated titanium dioxide. The subsequent process is the same as the prior art, so it is not described here.

[0039] Example 2

[0040] A coating process based on wet-process phosphoric acid comprises the following steps:

[0041] S1: At a temperature of 90°C, 6.2 m 3 Wet-process phosphoric acid and 2t of aluminum hydroxide are mixed and reacted for 90 minutes to obtain a mixture;

[0042] S2: maintaining the temperature at 90° C. to mature the mixture for 55 to 65 minutes, 60 minutes in this embodiment;

[0043] S3: The aging product is first filtered by a filter press, and then the obtained filtrate is diluted until the concentration of the phosphate aluminum coating agent is 100-120 g / L in terms of P2O5. The concentration of the phosphate aluminum coating agent obtained in this embodiment is 110 g / L in terms of P2O5;

[0044] The titanium dioxide is coated by a parallel flow method using a sodium aluminate solution and a phosphorus aluminum coating agent prepared by S3. The specific steps are as follows:

[0045] S41: injecting titanium dioxide slurry (in terms of TiO2) into a coating device, stirring and measuring the concentration and adjusting it to within a qualified range to obtain slurry A. In this embodiment, the concentration of slurry A is 300 g / L in terms of TiO2;

[0046] S42: Adding a phosphate-aluminum coating agent to slurry A at a temperature of 70°C, wherein the amount of the phosphate-aluminum coating agent added is x times the amount of the titanium dioxide slurry added. 102 %, adjusting the pH to 6.1, and aging for 15 min to obtain slurry B;

[0047] S43: Adding a phosphate aluminum coating agent and a sodium aluminate solution to slurry B at a temperature of 70°C in parallel, wherein the amount of the phosphate aluminum coating agent added is x times the amount of the titanium dioxide slurry added. 202 %, and X 102 %+X 202 % = 2.4%, when the pH drops to 6.0, sodium aluminate solution is added to control the pH to 6.0-7.5. The concentration of sodium aluminate solution is 220 g / L in terms of Al2O3, and the amount added is Y 102 %, adding time is 60min and after aging, slurry C is obtained;

[0048] S44: Add sodium aluminate solution (concentration is the same as S43) to slurry C at a temperature of 70°C, wherein the amount of sodium aluminate solution is Y 202 %, the addition time was 20 min, and slurry D was obtained after aging for 20 min. After adding sodium aluminate solution, the pH of the slurry was 8.1;

[0049] S45: At a temperature of 70°C, aluminum sulfate solution with a concentration of 90 g / L in terms of Al2O3 and sodium aluminate solution (the concentration is the same as S43) are added to slurry D in parallel, wherein the amount of sodium aluminate added is Y 302 %, the amount of aluminum sulfate solution added is Y 402 %, and calculated as Al2O3 102 %+Y 202 %+Y 302 %+Y 402 % = 5.4%, and Y is calculated as Al2O3 302 %:Y 402 % = 2:1, the duration of the parallel flow is 130 min, the pH after the parallel flow is 8.1, and the slurry E is obtained after aging for 30 min;

[0050] S46: After adding dilute sulfuric acid to adjust the pH value of slurry E to 5.7, coated titanium dioxide slurry is obtained. The titanium dioxide slurry is washed, flash evaporated, and steam-powdered to obtain coated titanium dioxide. The subsequent process is the same as the prior art, so it is not described here.

[0051] Example 3

[0052] A coating process based on wet-process phosphoric acid comprises the following steps:

[0053] S1: At a temperature of 90°C, 6.2 m 3 Wet-process phosphoric acid and 2t of aluminum hydroxide are mixed and reacted for 90 minutes to obtain a mixture;

[0054] S2: maintaining the temperature at 90° C. to mature the mixture for 55 to 65 minutes, 60 minutes in this embodiment;

[0055] S3: The aging product is first filtered by a filter press, and then the obtained filtrate is diluted until the concentration of the phosphate aluminum coating agent is 100-120 g / L in terms of P2O5. The concentration of the phosphate aluminum coating agent obtained in this embodiment is 110 g / L in terms of P2O5;

[0056] The titanium dioxide is coated by a parallel flow method using a sodium aluminate solution and a phosphorus aluminum coating agent prepared by S3. The specific steps are as follows:

[0057] S41: injecting titanium dioxide slurry (in terms of TiO2) into a coating device, stirring and measuring the concentration and adjusting it to within a qualified range to obtain slurry A. In this embodiment, the concentration of slurry A is 300 g / L in terms of TiO2;

[0058] S42: Adding a phosphate-aluminum coating agent to slurry A at a temperature of 70°C, wherein the amount of the phosphate-aluminum coating agent added is x times the amount of the titanium dioxide slurry added. 103 %, adjusted the pH to 6.3, and after aging for 15 min, slurry B was obtained;

[0059] S43: Adding a phosphate aluminum coating agent and a sodium aluminate solution to slurry B at a temperature of 70°C in parallel, wherein the amount of the phosphate aluminum coating agent added is x times the amount of the titanium dioxide slurry added. 203 %, and X 103 %+X 203 % = 2.6%, when the pH drops to 6.0, sodium aluminate solution is added to control the pH to 6.0-7.5. The concentration of sodium aluminate solution is 220 g / L in terms of Al2O3, and the amount added is Y 103 %, adding time is 60min and after aging, slurry C is obtained;

[0060] S44: Add sodium aluminate solution (concentration is the same as S43) to slurry C at a temperature of 70°C, wherein the amount of sodium aluminate solution is Y 203 %, the addition time was 20 min, and slurry D was obtained after aging for 20 min. After adding sodium aluminate solution, the pH of the slurry was 8.3;

[0061] S45: At a temperature of 70°C, aluminum sulfate solution with a concentration of 90 g / L in terms of Al2O3 and sodium aluminate solution (the concentration is the same as S43) are added to slurry D in parallel, wherein the amount of sodium aluminate added is Y 303 %, the amount of aluminum sulfate solution added is Y 403 %, and calculated as Al2O3 103 %+Y 203 %+Y 303 %+Y 403 % = 5.8%, and Y is calculated as Al2O3 303 %:Y 403 % = 2:1, the duration of parallel flow is 130 min, the pH after parallel flow is 8.3, and slurry E is obtained after aging for 30 min;

[0062] S46: After adding dilute sulfuric acid to adjust the pH value of slurry E to 5.8, coated titanium dioxide slurry is obtained. The titanium dioxide slurry is washed, flash evaporated, and steam-powdered to obtain coated titanium dioxide. The subsequent process is the same as the prior art, so it is not described here.

[0063] Example 3

[0064] A coating process based on wet-process phosphoric acid comprises the following steps:

[0065] S1: At a temperature of 90°C, 6.2 m 3 Wet-process phosphoric acid and 2t of aluminum hydroxide are mixed and reacted for 90 minutes to obtain a mixture;

[0066] S2: maintaining the temperature at 90° C. to mature the mixture for 55 to 65 minutes, 60 minutes in this embodiment;

[0067] S3: The aging product is first filtered by a filter press, and then the obtained filtrate is diluted until the concentration of the phosphate aluminum coating agent is 100-120 g / L in terms of P2O5. The concentration of the phosphate aluminum coating agent obtained in this embodiment is 110 g / L in terms of P2O5;

[0068] The titanium dioxide is coated by a parallel flow method using a sodium aluminate solution and a phosphorus aluminum coating agent prepared by S3. The specific steps are as follows:

[0069] S41: injecting titanium dioxide slurry (in terms of TiO2) into a coating device, stirring and measuring the concentration and adjusting it to within a qualified range to obtain slurry A. In this embodiment, the concentration of slurry A is 300 g / L in terms of TiO2;

[0070] S42: Adding a phosphate-aluminum coating agent to slurry A at a temperature of 70°C, wherein the amount of the phosphate-aluminum coating agent added is x times the amount of the titanium dioxide slurry added. 104%, adjusting the pH to 6.5, and aging for 15 min to obtain slurry B;

[0071] S43: Adding a phosphate aluminum coating agent and a sodium aluminate solution to slurry B at a temperature of 70°C in parallel, wherein the amount of the phosphate aluminum coating agent added is x times the amount of the titanium dioxide slurry added. 204 %, and X 104 %+X 204 % = 3.0%, when pH drops to 6.0, sodium aluminate solution is added to control pH 6.0-7.5. The concentration of sodium aluminate solution is 220 g / L in terms of Al2O3. The amount added is Y 104 %, adding time is 60min and after aging, slurry C is obtained;

[0072] S44: Add sodium aluminate solution (concentration is the same as S43) to slurry C at a temperature of 70°C, wherein the amount of sodium aluminate solution is Y 204 %, the addition time was 20 min, and slurry D was obtained after aging for 20 min. After adding sodium aluminate solution, the pH of the slurry was 8.5;

[0073] S45: At a temperature of 70°C, aluminum sulfate solution with a concentration of 90 g / L in terms of Al2O3 and sodium aluminate solution (the concentration is the same as S43) are added to slurry D in parallel, wherein the amount of sodium aluminate added is Y 304 %, the amount of aluminum sulfate solution added is Y 404 %, and calculated as Al2O3 104 %+Y 204 %+Y 304 %+Y 404 % = 6.0%, and Y is calculated as Al2O3 304 %:Y 404 % = 2:1, the duration of parallel flow is 130 min, the pH after parallel flow is 8.5, and slurry E is obtained after aging for 30 min;

[0074] S46: After adding dilute sulfuric acid to adjust the pH value of slurry E to 6.0, coated titanium dioxide slurry is obtained. The titanium dioxide slurry is washed, flash evaporated, and steam-powdered to obtain coated titanium dioxide. The subsequent process is the same as the prior art and will not be described here.

[0075] Comparative Example 1

[0076] This comparative example is basically the same as Example 1, except that pyrogenic phosphoric acid is used instead of wet-process phosphoric acid, and the filtration step is omitted.

[0077] Comparative Example 2

[0078] This comparative example uses wet-process phosphoric acid and sodium aluminate for coating: the slurry concentration is controlled to be 300g / L (in terms of TiO2), and the temperature is raised to 80°C at the same time; 3.0% NaSiO3 (in terms of SiO2) is added within 40min, and homogenized for 30min; wet-process phosphoric acid is added to adjust the pH to 3.0, and the adjustment is made for 50min, and the homogenization is made for 30min; 2.0% ZnCl2 and 3.0% Na2HPO4 solutions are added simultaneously within 60min, and the homogenization is made for 20min; H2SO4 is used to adjust the pH to 5.0, and the adjustment is completed within 40min, and the homogenization is made for 30min; the temperature is lowered to 40°C; Al2(SO 4)3 is added within 40min to adjust the pH to 2.0, and the homogenization is made for 30min; sodium aluminate is added within 40min to adjust the pH to 10.0, and the homogenization is made for 30min; pH is adjusted to 5.5 with dilute H2 SO4, and the adjustment is made for 30min, and the homogenization is made for 120min; and the coated titanium dioxide is obtained after washing, flash evaporation, and steam powder.

[0079] The specific components and contents of the wet-process phosphoric acid and pyrogenic phosphoric acid used in the examples or comparative examples are shown in Table 1:

[0080] Table 1

[0081]

[0082] The test data of blue light whiteness, titanium dioxide qualified rate and production cost of Examples 1-4 and Comparative Examples 1-2 are as follows:

[0083] Table 2

[0084] Example 1 Example 1 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Pass rate (%) 95.6% 95.4% 95.6% 95.7% 97.2% 75.1%

[0085] Since the main indicator of the first-class LR952 titanium dioxide is blue light whiteness ≥ 94.5, it can be seen from Table 2 that the qualified rate of LR952 titanium dioxide after using wet phosphoric acid is close to that of pyrophosphoric acid, but much higher than the qualified rate of LR952 titanium dioxide using sodium metaaluminate and wet phosphoric acid in the existing technology. The cost of wet phosphoric acid compared with pyrophosphoric acid is shown in Table 3:

[0086] Table 3

[0087]

[0088] As can be seen from Table 3, the production cost is greatly reduced after using wet-process phosphoric acid instead of pyro-process phosphoric acid, and an average of 297,339.75 yuan can be saved per month.

[0089] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

Claims

1. A coating process based on wet-process phosphoric acid, characterized in that: The preparation method of the aluminum phosphate coating agent is carried out by using a sodium aluminate solution and an aluminum phosphate coating agent, and the aluminum phosphate coating agent comprises the following steps: S1: mixing wet-process phosphoric acid and aluminum hydroxide to obtain a mixture; S2: ripening the mixture; S3: Filter and dilute the matured product to obtain a phosphate-aluminum coating agent.

2. The coating process based on wet-process phosphoric acid according to claim 1, characterized in that: The molar ratio of wet-process phosphoric acid to aluminum hydroxide in S1 is 3:

1.

3. The coating process based on wet-process phosphoric acid according to claim 1, characterized in that: The filtration conditions in S3 are that the filter cloth is polypropylene and the air permeability is 30L / m 3 ·s.

4. The coating process based on wet-process phosphoric acid according to claim 1, characterized in that: The ripening time in S2 is 55-65 minutes.

5. The coating process based on wet-process phosphoric acid according to claim 1, characterized in that: The concentration of the aluminum-phosphorus coating agent in S3 is 100-120 g / L in terms of P2O5.

6. A coating process based on wet-process phosphoric acid according to any one of claims 1 to 5, characterized in that: The specific steps of encapsulation are as follows: S41: injecting a quantitative titanium dioxide slurry into a coating device, stirring, measuring the concentration and adjusting it to within a qualified range to obtain slurry A; S42: adding a phosphate aluminum coating agent to slurry A, adjusting the pH, and aging to obtain slurry B; S43: adding a phosphate aluminum coating agent and a sodium aluminate solution to slurry B in parallel, and aging to obtain slurry C; S44: adding the sodium aluminate solution into the slurry C, and obtaining the slurry D after aging; S45: adding aluminum sulfate solution and sodium aluminate solution to slurry D in parallel, and obtaining slurry E after aging; S46: Adjust the pH value of slurry E to obtain coated titanium dioxide slurry.

7. A coating process based on wet-process phosphoric acid according to claim 6, characterized in that: The pH value of the slurry B obtained after aging was 6.0-6.

5.

8. A coating process based on wet-process phosphoric acid according to claim 7, characterized in that: The total mass ratio of the phosphorus aluminum coating agent added in S42 and S43 to titanium dioxide is 2.2-3% in terms of P2O5, and the pH value of the slurry C obtained after aging is controlled to be 6.0-7.

5.

9. The coating process based on wet-process phosphoric acid according to claim 6, characterized in that: The pH value of the slurry D obtained after aging was 8.0-8.

5.

10. The coating process based on wet-process phosphoric acid according to claim 6, characterized in that: The total mass ratio of sodium aluminate and aluminum sulfate added in S43, S44 and S45 to titanium dioxide is 5.0-6.0% in terms of Al2O3, and the pH value of the slurry E obtained after aging is 8.0-8.5; the pH value of the coated titanium dioxide slurry obtained in S46 is 5.5-6.0.

Citation Information

Patent Citations

  • Preparation method of special high-covering-power titanium dioxide for papermaking

    CN111040475A

  • Preparation method of high-retention and high-light-fastness titanium dioxide water slurry for papermaking

    CN114657813A

  • Preparation method of titanium dioxide for decorative paper

    CN114736536A

  • Titanium dioxide coating method

    CN117603596A

  • High-performance titanium dioxide pigment and preparation method therefor

    WO2024221721A1